A mathematical framework for managing interactive communication distortions in exascale organizations - Saeidi Ramyani Saleh; Ehsan Mousavi Khaneghah; Nosratollah Shadnoush; Araz R Aliev (Cogent Business & Management, 2018)
Increased complexity of functions makes the need for interactions and communications with other organizations important, and complexity of the environment of twenty-first-century organizations gives prominence to the need for conceptual redefining in these organizations and creating the concept of twenty-first-century ecosystems to perform activities. The nature of these events is such that they will be created during the life of the system, and in the absence of a framework to deal with them, they will cause organizations' activities failure. This paper introduces a framework for dealing with and managing interactive distortions at the level of twenty-first century ecosystems in a way that it would be able to re-establish the organization's communications with other organizations based on the proposed mathematical framework and identify the nature of interactive distortion and its impacts on the elements, organizations, and ecosystem without having to fail at ecosystem level, through redefining the ecosystem member organization based on a non-Euclidean space.
Keywords: 650